Sleep quality of mothers of newborns admitted to the Neonatal Intensive Care Unit (Research, Society and Development, 2020)
Objective: To verify the quality of sleep of mothers who have a newborn admitted to the Neonatal Intensive Care Unit. Methodology: This is a descriptive, exploratory, cross-sectional study, with a quantitative approach to the variables. It took place in a maternity hospital in the city of Manaus, with the participation of 120 women over the age of 18 years, with a minimum of 72 hours postpartum and with newborns in intensive care. This study used the Pittsburgh Sleep Quality Index, the State Anxiety Inventory and the Edinburgh Postpartum Depression Scale, using a structured questionnaire. The data were analyzed using SPSS software version 21, a descriptive analysis was performed considering the measures of central tendency. An analysis was performed associating sleep quality scores with the variables of anxiety and postpartum depression. Results: It was found that about 79.2% (n = 95) of the participants had problems regarding sleep quality. Among the most cited sleep problems are: waking up in the middle of the night or very early in the morning, getting up to use the bathroom, feeling very hot and not being able to sleep within half an hour. About 70% (n = 84) had pathological anxiety, however, only 33% (n = 40) were likely to have postpartum depression. Conclusion: The hospitalization of a newborn, linked to other environmental and social factors, influences the sleep of these mothers, affecting the quality of life of this puerperal woman, in order to be associated with anxiety and may contribute to the probability of postpartum depression.